Improved magneto-electric properties of LaFeO3 in La0.8Gd0.2Fe0.97Nb0.03O3. Issue 4 (March 2018) - Mitra, A.; Mahapatra, A.S.; Mallick, A.; Shaw, A.; Bhakta, N.; Chakrabarti, P.K.
Abstract: Samples of LaFeO3 (LFO) and La0.8 Gd0.2 Fe0.97 Nb0.03 O3 (LGFNO) are prepared by solid state reaction method. The combination of these ions (3d and 4d) is chosen to enhance the magnetic and ferroelectric property of the multiferroic LFO. Crystallographic phase analyses of LFO and LGFNO are carried out by Rietveld method using MAUD program which confirms the successful substitution of Gd 3+ and Nb 5+ in the lattice of LFO. Zero field cooled (ZFC) and field cooled (FC) magnetizations of LGFNO are measured in the range of 300–5 K in vibrating sample magnetometer (VSM) which shows an antiferromagnetic (AFM) to ferromagnetic (FM) phase transition below 85 K. Magnetic hysteresis loops recorded at 300 and 5 K exhibits the enhancement of magnetization of the co-doped sample (LGFNO) at 300 (2.02 times) and 5 K (31.7 times) with reference to LFO. Dielectric properties such as dielectric constant ( ε ′ ) and loss tangent (tanδ) of LFO and LGFNO are measured with the variation of temperature from 300 K up to 900 K and also with the variation of frequency from 42 Hz to 5 MHz. The thermal variation of dielectric constant ( ε ′ ) shows ferroelectric to paraelectric phase transition of LGFNO at 780 K. Polarization vs. electric field (P-E) loops of these samples recorded at 300 K indicate the onset of ferroelectric ordering with enhanced polarization of LGFNO compared to that of LFO. The dielectric constant of LGFNO measured in presence and absence of magnetic field confirms that the samples are type-II multiferroic with positive magneto-electric coupling and also the value of magneto-capacitance (MC) of LGFNO is enhanced compared to that of LFO which suggests that the co-doping with Gd 3+ and Nb 5+ ions in place of La 3+ and Fe 3+ ions also enhance the magneto-electric coupling.